Mandibular reconstruction with polyetheretherketone computer designed implant - Oré-Acevedo, Juan Francisco (2014)
A 22 years old male was referred to emergency for a gunshot trauma that involves the inferior third of the face with extension to the both submandibular and submental regions. The patient presented at the inferior half of the mandible, bodies and symphysis, a comminuted mandible fracture and two displaced fractures at the upper half of the mandible; though no teeth were missing. He underwent at emergency an open reduction and osteosynthesis with wires. A polyetheretherketone (PEEK) computer designed implant was placed to replace the lost bone tissue and restore the facial aesthetics. The PEEK implant is actually a new, simple and versatile method for complex mandibular reconstructions.